SISTEM PENILAIAN KINERJA KONSULTAN PERENCANA DALAM MENANGANI PROYEK PERENCANAAN BANGUNAN GEDUNG - Astawa Diputra, I Gede (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009)
Evaluation of building design consultant performance is needed, because most of strategic decisions and project costs depend on the consultant performance that is implemented in project design documents. The Analytical Hierarchy Process (AHP) method can be used as a reference for assessing the consultant performance in more detail and measurable. The hierarchy of assessment criterions was obtained from the interview in which the respondents were building design experts and it was combined with relevant literatures. The analysis using the AHP method was conducted to compare the importance level of criterion using pair-comparison matrixes. The weight of criterion and sub criterion were calculated by using eigen vector. The result of this study indicates that Quality of Design Document is the most important criterion (41,8%), followed by Relevancy with Term Of Reference (26%), Time Schedule ( 17,7%), and Design Cost (14,5%), which presented at level 2. At level 3, Consistency of Design Document is the most important criterion (13,9%), followed by Constructability of Design Document (11,3%), Accuracy of Design Document (10,6%), and so on. The last criterion, which has the smallest assessment weight, is the Goal Achievement of the Preparation Phase (4,6%). At level 4, Consistency among Engineering Drawing Document, Specification and Cost Estimate is the most important sub-criterion (6,9%), followed by Rational Time Schedule (5,8%), Equivalency of Remuneration with Project Requirement (5,7%) and so on. The last criterion is positioned by Explanation of Construction Material, which has the smallest assessment weight (0,7%). Based on the assessment hierarchy, which has been completed with global weight of all criterions, hence the tables of assessment system for building design consultant performance can be made. Accordingly, the consultants can be classified according to their performance levels.
Keywords: Performance assessment system, Building design consultant, Analytical Hierarchy Process